Vacancy‐induced LaMnO3 Perovskite as Bifunctional Air‐breathing Electrode for Rechargeable Lithium‐Air Battery. Issue 33 (1st September 2022) - Devi, Vaithiyanathan Sankar; Athika, Mattath; Elumalai, Perumal
Abstract: Development of cost‐effective efficient bifunctional electrocatalysts is indispensable for commercialization of metal‐air batteries. Here, vacancy‐induced nanostructured LaMnO3 perovskite was generated by a facile hydrothermal method and explored as a bifunctional air‐breathing electrode for rechargeable Lithium‐Air battery. Materials characterizations confirmed the formation of the nanostructured LaMnO3 with anion and cation vacancies. The LaMnO3 electrocatalyst on rotating ring disc electrode study showed excellent oxygen reduction reaction and oxygen evolution reaction activities in 0.1 M KOH electrolyte. The oxygen vacancies associated with the LaMnO3 acted as catalyst centre and promoted reaction rate for the ORR and OER. Laboratory prototype CR‐2032 air‐coin cell was fabricated using the LaMnO3 as air‐breathing electrode, resulted open circuit voltage 3.3 V for more than 5 days and high discharge capacity of 3100 mA h g −1 at current density of 50 mA g −1 . Further, once charged air‐coin cell could power an LED for more than 24 h continuously. Abstract : Vacancy‐induced nanostructured LaMnO3 perovskite was generated by a facile hydrothermal method and explored as an air‐breathing electrode for Lithium‐Air battery. The vacancies in the LaMnO3 acted as catalyst centre and promoted rates for the ORR (Oxygen reduction reaction) and OER (Oxygen evolution reaction). Prototype CR‐2032 Li‐Air battery using the LaMnO3 as air‐breathing electrode resulted open circuit voltage 3.3 V and high discharge capacity of 3100 mA h g −1 . The air‐battery could power an LED for more than 24 h continuously.